Î³-ray pre-irradiated grafting of polytetrafluoroethylene film membrane - Idris, A. (Penerbit UTM Press, 2014)
The changes induced by Î³-ray pre-irradiated grafting of polytetrafluoroethylene (PTFE) with alkalo-amines such as Monoethanolamine (MEA), Diethanolamine (DEA) and Methyldiethanolamine (MDEA) solvents were investigated. Samples of the commercially available fluoropolymer, i.e. PTFE film membranes were irradiated with 60Co source Î³-radiation with absorbed doses of 30 to 90 kGy. Effects of the grafting conditions of the amines onto the pre-irradiated PTFE, such as grafting time, reaction temperature and pre-irradiation doses on the resulting grafting yield are reported. The grafted PTFE was characterized by the FT-IR spectroscopy and FESEM.The gravimeteric analysis showed that the maximum grafting yield obtained is 2.9 for the 30 kGy irradiated MDEA grafted PTFE (MDEA-g-PTFE) at 10 min grafting time. However, at 60 min grafting time the maximum grafting yield reduced to 1.05 for the same sample. Consequently, therefore, for the low dose Î³-ray pre-irradiated samples, the effects of applied dose and grafting time were found to be remarkably insignificant. Â© 2014 Penerbit UTM Press. All rights reserved.